A completely noninvasive method of dissolved oxygen monitoring in disposable small‐scale cell culture vessels based on diffusion through permeable vessel walls. (1st December 2013) - Gupta, Priyanka A.; Ge, Xudong; Kostov, Yordan; Rao, Govind
<x xml:space="preserve">Abstract</x> Disposable cell culture vessels are extensively used at small scales for process optimization and validation, but they lack monitoring capabilities. Optical sensors that can be easily adapted for use in small‐scale vessels are commercially available for pH, dissolved oxygen (DO), and dissolved carbon dioxide (DCO2). However, their use has been limited due to the contamination and compatibility issues. We have developed a novel solution to these problems for DO monitoring. Oxygen diffusion through permeable vessel wall can be exploited for noninvasive monitoring. An optical oxygen sensor can be placed outside the oxygen permeable vessel wall thereby allowing oxygen diffusing through the vessel wall to be detected by the sensor. This way the sensor stays separate from the cell culture and there are no concerns about contaminants or leachants. Here we implement this method for two cell culture devices: polystyrene‐made T‐75 tissue culture flask and fluorinated ethylene propylene (FEP)‐made Vuelife® cell culture bag. Additionally, mammalian and microbial cell cultures were performed in Vuelife® cell culture bags, proving that a sensor placed outside can be used to track changes in cell cultures. This approach toward noninvasive monitoring will help in integrating cell culture vessels with sensors in a seamless manner. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:172–177, 2014